Analisis Pemerolehan Bahasa Pada Anak Usia 2 Tahun 11 Bulan Dengan Menggunakan Teori Brown - Jayanti Utami; Wienike Dinar Pratiwi; Een Nurhasanah; Hendra Setiawan (Jurnal Ilmiah Wahana Pendidikan, 2022)
Research on the analysis of children's language acquisition using Brown's theory is formulated with (1) how is Brown's Mean Length of Utterance (MLU) measured?, and (2) How are the results of the analysis of language acquisition in children 2 years 11 months old using Brown's theory? From the formulation of the problem mentioned above, the objectives of this study are (1) to explain about the Mean Length of Utterance (MLU) measurement according to Brown, and (2) to describe the results of the analysis of language acquisition in children aged 2 years 11 months using Brown's theory. In this study using a descriptive qualitative method and made a child with the age of 2 years 11 months named Ashalin as the subject in this study. From the results of the study, it has been shown that Shalin's language acquisition is in stage II, which means language acquisition is still low because at Shelin's current age, she is 2 years 11 months or 35 months with data obtained in the form of 162 morphemes and 249 utterances.